The effect of different emotional states on olfactory perception: A preliminary study. (23rd August 2018) - Hamakawa, Masayuki; Okamoto, Tsuyoshi
Abstract: Emotion evoked by odours can be determined or modulated by several factors, including odorant–receptor interactions and olfactory experiences. As a result of these factors, some odours can induce an emotional discrepancy, such as a conflict between innately determined and experience‐based emotions. This study examined whether the difference between two subjective ratings, pleasantness and liking, for an odour can influence olfactory perception, and explored whether the emotional discrepancy had any effect on olfaction. We conducted a psychophysical experiment wherein 12 participants (six women and six men, mean age = 22.0 years) evaluated 36 odours. Participants were instructed to evaluate each odorant in terms of four qualities: (i) pleasantness, (ii) liking, (iii) olfactory perceptual descriptors, and (iv) odour intensity. Participants were also asked to note the difference between pleasantness and liking, whereby the former referred to instinctive and innate feelings and the latter to experience‐based and acquired feelings. Ten odorants exhibited a discrepancy between pleasantness and liking ratings. Another 10 odorants exhibited a significant relationship between the choice of perceptual descriptors and intensity; this was not true of the 10 discrepant odorants. This preliminary study showed that differences in pleasantness and liking ratings can affect the selection of olfactory descriptors, according to odour intensity. The findings suggest that olfactory lexical semantic representations could be confused by discrepant odour‐evoked emotions. Abstract : Psychophysical experiments demonstrated a difference between subjective ratings for an odour, innate pleasantness and acquired liking. Our results could indicate that the difference influenced the selection of olfactory perceptual descriptors according to odor intensity.